Identification of a new locus at 16q12 associated with time to asthma onset - Sarnowski,C; Sugier,PE; Granell,R; Jarvis,D; Dizier,MH; Ege,M; Imboden,M; Laprise,C; Khusnutdinova,EK; Freidin,MB; Cookson,WO; Moffatt,M; et al. (Journal of Allergy and Clinical Immunology, 2016)
BackgroundAsthma is a heterogeneous disease in which age of onset plays an important role.ObjectiveWe sought to identify the genetic variants associated with time to asthma onset (TAO).MethodsWe conducted a large-scale meta-analysis of 9 genome-wide association studies of TAO (total of 5462 asthmatic patients with a broad range of age of asthma onset and 8424 control subjects of European ancestry) performed by using survival analysis techniques.ResultsWe detected 5 regions associated with TAO at the genome-wide significant level (P < 5 × 10−8). We evidenced a new locus in the 16q12 region (near cylindromatosis turban tumor syndrome gene [CYLD]) and confirmed 4 asthma risk regions: 2q12 (IL-1 receptor–like 1 [IL1RL1]), 6p21 (HLA-DQA1), 9p24 (IL33), and 17q12-q21 (zona pellucida binding protein 2 [ZPBP2]–gasdermin A [GSDMA]). Conditional analyses identified 2 distinct signals at 9p24 (both upstream of IL33) and 17q12-q21 (near ZPBP2 and within GSDMA). Together, these 7 distinct loci explained 6.0% of the variance in TAO. In addition, we showed that genetic variants at 9p24 and 17q12-q21 were strongly associated with an earlier onset of childhood asthma (P ≤ .002), whereas the 16q12 single nucleotide polymorphism was associated with later asthma onset (P = .04). A high burden of disease risk alleles at these loci was associated with earlier age of asthma onset (4 vs 9-12 years, P = 10−4).ConclusionThe new susceptibility region for TAO at 16q12 harbors variants that correlate with the expression of CYLD and nucleotide-binding oligomerization domain 2 (NOD2), 2 strong candidates for asthma. This study demonstrates that incorporating the variability of age of asthma onset in asthma modeling is a helpful approach in the search for disease susceptibility genes.